Disturbance rejection in fuzzy systems based on two dimensional modified repetitive-control. (November 2020) - Sweety, C. Antony Crispin; Mohanapriya, S.; Kwon, O.M.; Sakthivel, R.
Abstract: This paper concerns with the issues of designing an improved-equivalent-input-disturbance (IEID) based robust two dimensional modified repetitive control (2D MRC) for a class of fuzzy systems in the presence of aperiodic disturbances. Specifically, IEID-estimator is implemented to the 2D MRC systems that estimates all types of disturbances and compensates them for assuring robust stability. In particular, the proposed 2D MRC system has two different type of behaviours such as continuous control and discrete learning independently. To obtain gains of the observer and the controller, an adequate set of robust stability conditions is derived in the form of a linear-matrix-inequalities. Finally, simulation results for three numerical examples are provided to depict the efficacy of the proposed control technique. Highlights: An IEID-based state tracking control mechanism is proposed for T-S Fuzzy systems. To be specific, 2D MRC is designed in order to get the exact tracking performance. The acquired theoretical outcomes are validated by the numerical simulation results.